Shadow economy and financial development: evidence from developed and developing countries - Chan, Zi Kang; Chong, Wen Rui; Chong, Xian Ming; Mak, Chi Ling; Tan, Chee Sheun (2021)
Shadow economy is a serious issue in every nation’s economy in the world. Shadow economy is an unregulated economic activity such as corruption, tax evasion and money laundering that can hinders the development of financial sector of a country. Hence, the purpose of this paper is to study the impact of shadow economy on financial development for 33 developed countries and 124 developing countries over the period of 1991 - 2017 with Two-Step Robust System Generalized Method of Moments (GMM) dynamic panel estimators. There are control variables such as natural resources, trade openness, technological innovation and human capital were used in study. The results summarized that shadow economy has a negative relationship on financial development in both developed countries and developing countries. Natural resources showed insignificant connection on financial development for developed and developing countries, while trade openness and technological innovation showed significant connection on financial development for developed and developing countries. For human capital, it showed a positive relationship with financial development in developed countries. However, it showed a negative relationship with financial development on developing countries.